answersLogoWhite

Top Answer
User Avatar
Wiki User
Answered 2009-04-09 02:29:32

3(p+7) - (4p-1) = -5(2p-3) + 1 Multiplying out the brackets: 3p + 21 - 4p + 1 = -10p + 15 + 1 Simplifying: 22 - p = 16 - 10p 9p = -6 p = -2/3 To check, you could substitute p = -2/3 into the original equation and check that it holds.

001
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
๐Ÿ˜‚
0
User Avatar

Your Answer


Copyright ยฉ 2021 Multiply Media, LLC. All Rights Reserved. The material on this site can not be reproduced, distributed, transmitted, cached or otherwise used, except with prior written permission of Multiply.